Analysis of switched systems using the bond graph methods - Poyraz, M; Demir, Y; Gülten, A; Köksal, M (Pergamon-Elsevier Science Ltd, 1999)
In recent years, the analysis of switching systems has gained importance. In this paper, the formulation of state and output equations and solutions of switched-systems are presented by using the bond graph model with a new simple and more general switch definition. The theory is illustrated by a few examples and the output of the computer programme called BOMAS is presented. (C) 1999 The Franklin Institute. Published by Elsevier Science Ltd.
Keywords: switched systems; bond graph model